Myxoid High-Grade Endometrial Stromal Sarcoma: A Close Mimicker of Myxoid Leiomyosarcoma - Gudale, Neha Raosaheb; Saraf, Sonali; Gadgil, Nitin (Annals of Pathology and Laboratory Medicine, 2024)
Endometrial stromal sarcomas are rare malignant uterine tumors that make up approximately 10% of all uterine sarcomas, but only around 0.2% of all uterine malignancies. The high-grade category of ESS was reintroduced in the new World Health Organization (WHO) tumor classification system based on its distinct morphologic, immunohistochemical, and molecular characteristics. ZC3H7B-BCOR is a newly described subtype of high-grade endometrial stromal sarcoma that closely mimics the appearance of myxoid leiomyosarcoma. Although its frequency is reported as low, it may, in fact, be higher, as in the past these tumors were frequently misdiagnosed as leiomyosarcoma. We hereby present a case report of a 45-year-old female who presented with disseminated peritoneal deposits of HG-ESS, which had initially posed diagnostic challenges due to its myxoid background and resemblance to leiomyosarcoma. Detailed case history and immunohistochemistry evaluation guided us to the final diagnosis.